Medicated Nanofibers Fabricated Using NaCl Solutions as Shell Fluids in Modified Coaxial Electrospinning. (19th April 2016) - Wu, Yong-Hui; Yang, Chen; Li, Xiao-Yan; Zhu, Jia-Ying; Yu, Deng-Guang
Abstract : The present study reports the fabrication of medicated nanofibers for potential colon-targeted drug delivery using modified coaxial electrospinning, in which salt (NaCl) solutions were exploited as shell fluids to facilitate the preparation processes. A homemade concentric spinneret with an indented core capillary was developed to conduct the coaxial processes. Optical observations and scanning electron microscopic results demonstrated that the shell-to-core fluid flow rate ratio was a key parameter, which exerted a significant influence on the electrospinning processes and could be exploited to control the fibers' morphology and diameters. A scaling law ofD = 0.173 F - 0.531 (R 2 = 0.9976 ) was built, by which the nanofibers' sizes can be predicted and manipulated easily. X-ray diffraction and attenuated total reflected FTIR tests verified that the medicated nanofibers were essentially a polymeric nanocomposite and the guest drug diclofenac sodium (DS) had fine compatibility with the host polymer. All the drug was encapsulated in the filament-forming carrier. In vitro dissolution experiments demonstrated that the medicated nanofibers could free the drug in a neutral condition, suggesting potential colon-targeted drug delivery applications. Ex vivo tests demonstrated that the medicated fiber mats could enhance the transmembrane of DS. Based on coaxial electrospinning, a new strategy is successfully developed for creating medicated nanomaterials.